- #1
erba
- 10
- 1
We have a wave ψ(x,z,t). At t = 0 we can assume the wave to have the solution (and shape)
ψ = Q*exp[-i(kx)]
where k = wavenumber, i = complex number
The property for a Fourier transform of a time shift (t-τ) is
FT[f(t-τ)] = f(ω)*exp[-i(ωτ)]
Now, assume ψ(x,z,t) is shifted in time. Thus, ψ(x,z,t) = P(x,z,t-τ). And I want to express the shifted version of ψ (i.e. P) in the frequency domain. Me myself think this is done as:
FT[P(x,z,t-τ)] = Q(x,z,ω)*exp[-i(kx)]*exp[-i(ωτ)] = Q(x,z,ω)*exp[-i(kx - ωτ)]
Though, my teacher claims that, when we assume the solution to be Q(x,z,ω)*exp[-i(kx - ωτ)], we have not necessarily transformed the it into the Fourier domain yet. He says that this solution can be given to a wave in the spatial-time domain as well.
I claim, and think that we have transformed it! But, I guess that my teacher is right and I am wrong.
So please, could you guide me through my confusion here?
PS. Hope the explanation of my question is good enough. Otherwise, ask me :)
ψ = Q*exp[-i(kx)]
where k = wavenumber, i = complex number
The property for a Fourier transform of a time shift (t-τ) is
FT[f(t-τ)] = f(ω)*exp[-i(ωτ)]
Now, assume ψ(x,z,t) is shifted in time. Thus, ψ(x,z,t) = P(x,z,t-τ). And I want to express the shifted version of ψ (i.e. P) in the frequency domain. Me myself think this is done as:
FT[P(x,z,t-τ)] = Q(x,z,ω)*exp[-i(kx)]*exp[-i(ωτ)] = Q(x,z,ω)*exp[-i(kx - ωτ)]
Though, my teacher claims that, when we assume the solution to be Q(x,z,ω)*exp[-i(kx - ωτ)], we have not necessarily transformed the it into the Fourier domain yet. He says that this solution can be given to a wave in the spatial-time domain as well.
I claim, and think that we have transformed it! But, I guess that my teacher is right and I am wrong.
So please, could you guide me through my confusion here?
PS. Hope the explanation of my question is good enough. Otherwise, ask me :)